De Handji aux Ténèbres de Robert Poulet: une invitation à l’onirisme réaliste - Quinaux, Éléonore Julie (Ponti/Ponts, 2021)
In the 1920s, Franz Hellens, by the publication of Réalités fantastiques, expressed his desire to create a literary work that mixes fantastic mode and realism that the reader can’t discern what belongs to the imagination or reality. This idea of unique synthesis of two universes hitherto separated can be found in the works of the Belgian writer Robert Poulet. Although it has maintained an ambiguous relationship with the German extremist ideology during the Second World War, we must note no author could match his mastery of a certain magical realism, or rather as it liked to say, poetic novel. It is therefore the peculiarities of this unique literary creation that we propose to demonstrate by analyzing two specific fictional productions, Handji and Les Ténèbres. Indeed, Poulet wishes to present in these works the devouring power of hallucination. This one, stemming from thinking of protagonists, reaches first to stifle their first designs to sink into a dream world. Then, by writing mechanisms gradually erased, it grabs the reader by allowing him more to distinguish what comes from the real and pure fictional production.